Coronary angiographic findings and outcomes in patients with sudden cardiac arrest without ST-elevation myocardial infarction: A SWEDEHEART study. (May 2018) - Wester, Axel; Mohammad, Moman A.; Andell, Pontus; Rylance, Rebecca; Dankiewicz, Josef; Friberg, Hans; James, Stefan; Omerovic, Elmir; Erlinge, David; Koul, Sasha
Abstract: Background/aim: Sudden cardiac arrest (SCA) has a substantial mortality rate and the acute coronary syndrome constitutes the major cause. Post-resuscitation electrocardiogram ST-elevation SCA (STE-SCA) is a strong indication for emergency coronary angiography, but the role of early angiography and PCI in patients without ST-elevation (NSTE-SCA) remains to be established. This paper aimed to describe this patient group and evaluate the prognostic effect of early PCI in a large nationwide cohort of NSTE-SCA patients undergoing coronary angiography. Methods: Data from SCAAR (Swedish Coronary Angiography and Angioplasty Registry) and RIKS-HIA (Register of Information and Knowledge about Swedish Heart Intensive Care Admissions) on 4308 SCA patients in Sweden between 2005 and 2016 were descriptively analyzed and related to mortality within 30-days in both unadjusted and adjusted analyses using Cox proportional hazard models. Results: NSTE-SCA patients had more often serious comorbidities than STE-SCA patients. Among NSTE-SCA patients, 36.4% had no significant coronary artery stenosis while severe coronary stenosis (≥90%) was present in 43.9% (1271/2896). In NSTE-SCA patients with significant stenosis (≥90%), PCI was performed in 59.2% (753/1271) with an increased unadjusted 30-day mortality (40.9% vs. 32.7%; p = .011). However, after adjustments for confounders, no difference in mortality was observed (hazard ratio 1.07; 95% CI 0.84–1.36; p = .57). Conclusion: In resuscitated SCA patients without ST-elevation who underwent coronary angiography, this large retrospective study found severe coronary artery stenosis in 43.9% but found no clear benefit of early PCI. Prospective randomized controlled trials are needed to accurately define the role of coronary angiography and PCI in post-resuscitation care.